The Morphologicial Investigations of Experimental Avian Encephalomyelitis in Turkey Embriyo - Yilmaz, F; Özer, H (Tubitak Scientific & Technological Research Council Turkey, 1999)
In this study; macroscopic and microscopic changes induced by Avian Encepholomyelitis Virus (AEV) in turkey embryos were investigated. For purpose 0,1 mi. AEV-VR (Van Roekel Strain) at Embriyo Infective Dose 50 of 10(-3) diluted in sterile saline at 1/10 ratio was inoculated into 7-day-old emriyonated turkey eggs via yolk sac. The most prominent macroscopic findings were loss of embryo movements, retardation in growth, cerebral edema, torticollis, cataract, deformities in the leg and feed. Microscopic lesions characterized by vascular proliferation, edema, gliosis, neuronal necrosis and degeneration in the brain, gliosis, neuronal degeneration and necrosis, in medulla spinalis, cataract in the eyes, hyalin degeneration, necrosis, and dystrophy in the skeletal muscles were observed.
Hindi Embriyosunda Deneysel Avian Encephalomyelitis (AE) Üzerinde Morfolojik İncelemeler
Keywords: avian encephalomyelitis; Turkey embryo; pathological findings; experimental infection